The impact of donor-orientation on the emission properties of chlorinated trityl radicals - Arnold, Mona E.; Toews, Robert; Schneider, Lars; Schmid, Jonas; Putra, Miftahussurur Hamidi; Busch, Michael; Groß, Axel; Deschler, Felix; Köhn, Andreas; Kuehne, Alexander J. C. (Advanced optical materials, 2025)
Chlorinated trityl radicals functionalized with electron-donating groups are promising red-emitting materials for optoelectronic and spintronic applications, overcoming the spin-statistical limit of conventional emitters. Donor functionalization induces charge transfer character, enhancing photoluminescence quantum yield, which depends on the donor strength and its orientation. However, donor-functionalized tris(trichlorophenyl)methyl radicals often show lower quantum yield than their perchlorinated derivatives, likely due to weaker donor-acceptor electronic coupling and enhanced non-radiative decay. A novel trityl derivative is presented with two additional chlorines that restrict the orientation of the donor to a nearly perpendicular arrangement toward the trityl plane, minimizing vibronic coupling and non-radiative losses. Spectroscopic and computational studies reveal that this steric constraint improves the photoluminescence quantum yield compared to the tris(trichlorophenyl)methyl analogs. These findings highlight the potential of donor-acceptor decoupling to enable efficient, redshifted emission, offering a design strategy for high-performance radical emitters.
Zuerst veröffentlicht: 21. April 2025
Gesehen am 07.10.2025